Dynamic Analysis of Ecological Efficiency in Urban Tourism Industry Based on Dea-malmquist Model - Guo, Yuchen; Guo, Jianwei (Informatica, 2024)
The development of urban tourism has to some extent driven urban economic growth. However, it involves multiple industries such as transportation, accommodation, entertainment, and catering, which can generate significant carbon emissions. To promote the tourism economy and environment's coordinated development, tourism ecological efficiency is proposed, and its measurement methods have also attracted attention. Therefore, a city tourism ecological efficiency measurement model based on tourism carbon emissions and DEA-Malmquist was proposed to improve the accuracy of measuring tourism ecological efficiency. This study first constructed a mixed model of least absolute shrinkage and selection operator-genetic algorithm-support vector regression to measure the carbon emissions of urban tourism industry. Subsequently, a DEA-Malmquist measurement means was constructed to evaluate the urban tourism's ecological efficiency. The relative error and absolute error of the proposed intelligent model were 2.005% and 2.005%, respectively, which were significantly better than the comparison models. The average carbon emission from leisure vacation activities, sightseeing, business trips, and visiting relatives and friends was 171100, 126700, 72300, and 61200 tons. The overall tourism ecological efficiency of this province showed a fluctuating trend. The technical efficiency decreased from its highest point of 0.774 in 2019 to its lowest point of 0.706 in 2020, and then gradually rebounded to 0.759 in 2023. Therefore, this proposed method can effectively measure the carbon emissions and tourism ecological efficiency of cities. It has practical operability and can provide an effective path for promoting tourism economy and ecological environment's balanced development.